2018
DOI: 10.1186/s12951-018-0407-5
|View full text |Cite
|
Sign up to set email alerts
|

A resonance Rayleigh scattering sensor for sensitive differentiation of telomere DNA length and monitoring special motifs (G-quadruplex and i-motif) based on the Ag nanoclusters and NAND logic gate responding to chemical input signals

Abstract: BackgroundDifferentiation of telomere length is of vital importance because telomere length is closely related with several deadly diseases such as cancer. Additionally, G-quadruplex and i-motif formation in telomeric DNA have been shown to act as a negative regulator of telomere elongation by telomerase in vivo and are considered as an attractive drug target for cancer chemotherapy.ResultsIn this assay, Ag nanoclusters templated by hyperbranched polyethyleneimine (PEI–Ag NCs) are designed as a new novel reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additionally, interactions of PEI-AgNCs with GQ or i-motifs result in slight changes in RRS intensities. 40 In an alternative experiment, genomic DNA extracted from samples is affixed to SERS probes, which are then deposited onto an SERS substrate composed of assembled silver nanoparticles (AgNPs), followed by SERS measurement. Greater telomere length leads to an increased number of telomere probes being attached, consequently producing a more prominent SERS signal.…”
Section: Uses Of Copper Nanoparticlesmentioning
confidence: 99%
“…Additionally, interactions of PEI-AgNCs with GQ or i-motifs result in slight changes in RRS intensities. 40 In an alternative experiment, genomic DNA extracted from samples is affixed to SERS probes, which are then deposited onto an SERS substrate composed of assembled silver nanoparticles (AgNPs), followed by SERS measurement. Greater telomere length leads to an increased number of telomere probes being attached, consequently producing a more prominent SERS signal.…”
Section: Uses Of Copper Nanoparticlesmentioning
confidence: 99%
“…In this sense, development of relevant biomarkers to assist the early-stage diagnosis is a priority. Telomerase is a ribonucleoprotein enzyme elongating telomeric DNA, whose differential expression in normal tissues and tumor cells makes it an attractive biomarker for HCC diagnostic and prognostic (Wang et al, 2018;Afshari et al, 2022;Manganelli et al, 2022). Researchers have found that quantitative assay of telomerase can provide a satisfactory positive rate for HCC diagnosis compared to alpha-fetoprotein (AFP) and PIVKA-II (Tzartzeva and Singal., 2018).…”
Section: Introductionmentioning
confidence: 99%